Peran Komunikasi Publik dalam Menyampaikan Nilai-nilai Positif Terhadap Anak di SDN 14 Indralaya - Johan Trimuda; Armasito Armasito (Jurnal Aksi Dosen dan Mahasiswa, 2025)
Public communication plays a strategic role in character formation and instilling positive values ​​in elementary school-aged children. However, limited media and educational communication strategies often hinder the internalization of moral and social values ​​in the school environment. This community service activity was conducted at SDN 14 Indralaya with the aim of improving the effectiveness of school public communication as a means of educating students about the values ​​of honesty, discipline, responsibility, and cooperation. Implementation methods included initial observation, mentoring, and the application of participatory and creative educational communication media. The results of the activity showed an increase in students' understanding of positive values ​​and more active involvement in the communication process in the school environment. In addition, teachers gained alternative communication strategies that were more contextual and child-friendly. This activity demonstrated that public communication designed in an educational and participatory manner can be an effective means of supporting character formation in elementary school children.